Cell Cycle Analysis of Candida albicans by Flow Cytometry - Shraddheya Patel; Satya Sahu; Narottam Acahrya (Bio-Protocol, 2023)
The cell cycle is a vital process of cell division that is required to sustain life. Since faithful cell division is critical for the proper growth and development of an organism, the study of the cell cycle becomes a fundamental research objective. Saccharomyces cerevisiae has been an excellent unicellular system for unraveling the secrets of cell division, and the process of synchronization in budding yeast has been standardized. Cell synchronization is a crucial step of cell cycle analysis, where cells in a culture at different stages of the cell cycle are arrested to the same phase and, upon release, they progress synchronously. The cellular synchronization of S. cerevisiae is easily achieved by a pheromone or other chemicals like hydroxyurea treatment; however, such methodologies seem to be ineffective in synchronizing cells of multimorphic fungi such as Candida albicans. C. albicans is a human pathogen that can grow in yeast, pseudohyphal, and hyphal forms; these forms differ in morphology as well as cell cycle progression. More importantly, upon subjecting to DNA replication inhibitors for synchronization, C. albicans develops hyphal structures and grows asynchronously. Therefore, here we describe a simple and easy method to synchronize C. albicans cells in the G1 phase and the subsequent analysis of cell cycle progression by using flow cytometry.